Teachers’ Perception About Islamic Values Integration Into Mathematics Learning Through Comics - Putri, Rizqa; Johar, Rahma; Munzir, Said (Jurnal Ilmiah Peuradeun, 2022)
Aceh is one of 34 provinces in Indonesia that has a local education goal, that is, the education is implemented based on Islamic values. The integration of Islamic values into mathematics learning can be implemented by using learning media. This research is an early phase of developmental research. The purpose of this study was to investigate teachers’ perceptions of the integration of Islamic values ​​into mathematics learning through comics. The participants were 40 junior high school mathematics teachers in Banda Aceh who join the PMRI workshop. Data were collected through an open-ended questionnaire consisting of 11 questions and then analyzed descriptively. The results showed that teachers (87.5%) believed that Islamic values and mathematics ​​are integrated; moreover, mathematics teachers and religion teachers play a major role in teaching Islamic values. The majority of teachers (95%) believed that the knowledge of Islamic values influences the way they teach. However, more than half of teachers (62.5%) had never attended a workshop or seminar, or read articles that discuss the integration of Islamic values ​​into mathematics learning through comics. The result of the study also showed that the mathematics comics in Islamic values were limited. Therefore, it is necessary to develop mathematics comics in Islamic values contexts.